AB0683 Trough infliximab levels and anti-infliximab antibodies in spondyloarthritis patients on treatment with low dose infliximab: a single centre cross-sectional study. (15th June 2017) - Patil, A; Upadhyaya, SK; Dawar, R; Vaishnav, B; Dadhaniya, N; Gupta, SJ; Handa, R
Abstract : Background: Infliximab (IFX) is an anti-TNF, chimeric, monoclonal antibody approved for use in refractory spondyloarthritis (SpA). Studies done in patients with Rheumatoid arthritis 1 and Inflammatory bowel disease 2 have demonstrated the clinical utility of the measurement of serum trough IFX and antibodies to IFX (ATI). In India, many centres including ours use IFX at lower doses of 3–5 mg/kg and on demand IFX treatment without the use of the loading dose IFX in SpA patients 3 . Data on the utility of measuring trough IFX and ATI levels and their correlation with disease activity in such group of patients is lacking. Objectives: To evaluate the co-relation between trough Infliximab levels and disease activity measures, viz ASDAS ESR and ASDAS CRP in SpA patients on low dose IFX therapy To compare the mean ASDAS- ESR/CRP scores between ATI positive and ATI negative patients Methods: Thirty-nine adult spondyloarthrtitis patients in the age group of 18–70 years, meeting the ASAAS classification criteria for peripheral and/or axial spondyloarthritis were recruited into the study. The inclusion criteria required the patients to have had received three or more infusions of IFX at 3–5 mg/kg/dose over the past 6 to 9 months. Blood samples were collected between two to three months after the previous IFX infusion for the measurement of the ATI and the trough IFX levels using the Matriks Biotek Shikari Q-ATI ELISA and Q-IFLIXI ELISA kits respectively. At the same time, disease activity of the patients was quantitated using ASDAS ESR and ASDAS CRP scores. Correlation between the ASDAS scores and the trough IFX levels was analysed by Pearson's product moment correlation assay. The difference in mean trough IFX and ASDAS scores between the ATI positive and ATI negative patients were assessed using Welch two sample t-test. Results: There was a moderately significant negative correlation between the trough IFX levels and the ASDAS-ESR (r = -0.69, p<0.001), ASDAS-CRP scores (r = -0.67, p<0.001) (Fig 1 ). ATI positive patients in comparison to ATI negative, had significantly higher ASDAS ESR and ASDAS CRP scores (Table 1 ). Conclusions: SpA patients from India on low dose, on demand IFX therapy, have both the trough IFX and ATI correlate significantly with the measures of disease activity. Therefore, these may be used in addition to clinical activity scores for a more cost effective on demand IFX therapy in SpA patients, especially in an expense constrained country like India. References: Laine J, JokirantaT, Eklund K, Vakevainen M, Puolakka K. Cost effectiveness of routine measuring of serum drug concentrations and anti-drug antibodies in treatment of rheumatoid arthritis patients with TNFα blockers. Biologicals: Targets and therapy.2016;10:67–73. Pallagi Kunstar E, Farkas K, Szepes Z et al. Utility of serum TNFα, infliximab trough level and antibody titres in inflammatory bowel disease. World J Gastroenterol. 2014;20:5031–5. Kumar A. Experience with anti-tumour necorsis factor-α therapy in India. APLAR journal of Rheumatology. 2006;9:136–41. Disclosure of Interest: None declared